Applications of nanotechnology in biodiesel combustion and post-combustion stages - Hosseinzadeh-Bandbafha, Homa; Kazemi Shariat Panahi, Hamed; Dehhaghi, Mona; Orooji, Yasin; Shahbeik, Hossein; Mahian, Omid; Karimi‑Maleh, Hassan; Kalam, Md Abul; Salehi Jouzani, Gholamreza; Mei, Changtong; Nizami, Abdul-Sattar; Guillemin, Gilles G.; et al. (Renewable and sustainable energy reviews)
Diesel fuel exhibits high efficiency, durability, and profitability for combustion engines but remains a major source of airborne pollutants, including particulate matter and nitrogen oxides. To address the urgent need for alternative energy sources and reduce greenhouse gas emissions, biodiesel has been developed as a potential replacement for petrodiesel. However, biodiesel combustion has its drawbacks, especially the emission of nitrogen oxides, which hinder its ability to replace petrodiesel sustainably. Nanotechnology has been proposed as a promising solution to improve biodiesel combustion and enhance its competitiveness against petrodiesel. Various studies have shown that both metallic and non-metallic nanoparticles can potentially enhance biodiesel performance during combustion, improving fuel combustion efficiency by 11.7% and 13.4% while reducing air pollutants such as carbon monoxide by 24.2% and 24.8% and unburned hydrocarbons by 11.5% and 25.3%, respectively. While both types of nanoparticles can potentially reduce greenhouse gas and particulate matter emissions, their impact on nitrogen oxide emissions varies. Non-metallic nanoparticles are more successful in reducing nitrogen oxide emissions, achieving reductions of up to 13.0%, while metallic nanoparticles have been shown to increase nitrogen oxides by 0.8% on average. In the post-combustion phase, nanoparticles can filter pollution from diesel engines with more than 99% efficiency, reducing friction, enhancing engine durability, preventing deposit formation, and reducing maintenance costs. However, using nanoparticles in biodiesel has several drawbacks, including toxicity to humans and ecosystems, high prices, lack of standardization, and limited understanding of their long-term effects. Further research is needed to address these constraints and ensure the safe and effective use of nanoparticles in biodiesel combustion. The potential benefits of nanotechnology for improving biodiesel combustion and reducing emissions can make this research field an exciting avenue for future research and development.